Observations of cold gas and star formation in dwarf S0 galaxies. Issue 3 (14th September 2021) - Ge, Xue; Gu, Qiu-Sheng; García-Benito, Rubén; Lu, Shi-Ying; Lei, Cheng-Long; Ding, Nan
ABSTRACT: Very little work has been done on star formation in dwarf lenticular galaxies (S0s). We present 2D spectroscopic and millimetre observations made by the Centro Astronómico Hispano Alemán (CAHA) 3.5-m optical and Institut de Radioastronomie Millimétrique (IRAM) 30-m millimetre telescopes, respectively, for a sample of four dwarf S0 galaxies with multiple star formation regions in the field environment. We find that, although most of the sources deviate from the star-forming main-sequence relation, they all follow the Kennicutt–Schmidt law. After comparing the stellar and H α kinematics, we find that the velocity fields of both stars and ionized gas show no regular motion and the velocity dispersions of both stars and ionized gas are low in regions with high star formation, suggesting that these star-forming S0 galaxies still have significant rotation. This view can be supported by the result that most of these dwarf S0 galaxies are classified as fast rotators. The ratio of the average atomic gas mass to stellar mass (47 per cent ) is much greater than that of the molecular gas mass to stellar mass (1 per cent ). In addition, gas-phase metallicities in star-forming regions are lower than those of non-star-forming regions. These results indicate that extended star formation may originate from the combination of abundant atomic hydrogen, a long dynamic time-scale, and a low-density environment.